Antimicrobial activity of essential oil from the fruits of Ammomum subulatum (International Journal of Pharmacy and Life Sciences, 2013)
The efficacy of seed extracts of Amomum subulatum Roxb. activity against bacterias such Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis, Escheria Coli. were studied. The minimum inhibitory concentration (MIC) of the extracts was determined using standard methods. Results obtained showed considerable inhibition against the bacteria tested showed considerable resistance at all concentrations of the extract. However the standard antibacterial drug Erythromycin exhibit superior activity than the extract. This activity was indicative of the possible means of finding pure active principles from natural source with possible high potency that could serve as a lead to the pharmaceuticals. The low concentration (MIC) activity of the extracts gives credence and scientific base for the claim therapeutic capabilities of Amomum subulatum as an anti-bacterial agent. The oil extract yield of the seed extracts was estimated to be 1.2 mL which is pale yellow in colour. The study provides the basis of use of this plant Amomum subulatum in treatment of infections caused by pathogens (bacteria) and the phytochemical found are implicated in having anti-bacterial properties.